High prevalence of human papillomavirus (HPV) in oral mucosal lesions of patients at the Ambulatory of Oral Diagnosis of the Federal University of Sergipe, Northeastern Brazil - RIBEIRO, Mariana Goveia Melo; MARCOLINO, Larissa Doddi; RAMOS, Bruna Ribeiro de Andrade; MIRANDA, Elaine Alves; TRENTO, Cleverson Luciano; JAIN, Sona; GURGEL, Ricardo Queiroz; SILVA, Márcia Guimarães da; DOLABELLA, Silvio Santana (Journal of Applied Oral Science, 2017)
The role of human papillomavirus (HPV) in oral carcinogenesis is still controversial as detection rates of the virus in oral cavity reported in the literature varies greatly. Objective The aim of this study was to evaluate the frequency of HPV infection and its genotypes in patients with oral lesions at the Ambulatory of Oral Diagnosis of the Federal University of Sergipe, Brazil. Material and Methods We conducted a molecular study with 21 patients (15 females) aged from two to 83 years with clinically detectable oral lesions. Samples were collected through exfoliation of lesions and HPV-DNA was identified using MY09/11 and GP5+/6+ primers. Genotyping was performed by multiplex PCR. Results Benign, premalignant and malignant lesions were diagnosed by histopathology. HPV was detected in 17 samples. Of these, HPV-6 was detected in 10 samples, HPV-18 in four and HPV-16 in one sample. When samples were categorized by lesion types, HPV was detected in two papilloma cases (2/3), five carcinomas (5/6), one hyperplasia (1/1) and nine dysplasia cases (9/11). Conclusion Unlike other studies in the literature, we reported high occurrence of HPV in oral lesions. Further studies are required to enhance the comprehension of natural history of oral lesions.